Association between quality of life and sleep time among community‐dwelling stroke survivors: Findings from a nationally representative survey. Issue 12 (6th November 2019) - Kim, Yoonjung; Moon, Hye‐Mi
Abstract : Aim: This study aimed to examine the association between quality of life and sleep time among adult stroke survivors. Methods: This cross‐sectional study used nationally representative data from the Korea National Health and Nutrition Examination Survey (2010–2013), and analyzed data on 504 adult stroke survivors. Results: Findings showed that stroke survivors' daily sleep time significantly varied by sex ( P  < 0.001), education ( P = 0.006) and body mass index ( P = 0.012). The EuroQOL‐5 Dimension index ( P  < 0.001), and its dimensions of mobility ( P = 0.011), usual activities ( P  < 0.001) and pain/discomfort ( P = 0.005) showed significant differences among people with different sleep times. In the final model, after adjusting for covariates, respondents who slept ≤5 h had odds ratios of 1.82 (95% confidence interval 1.05–3.16) for usual activities and 1.95 (95% confidence interval 1.16–3.27) for pain/discomfort compared with respondents who slept 6–8 h. Respondents who slept ≥9 h had an odds ratio of 3.03 (95% confidence interval 1.43–6.43) for usual activities compared with those who slept 6–8 h. Adjusted means for the EuroQOL‐5 Dimension index showed significant differences: 0.76 for ≤5 h, 0.85 for 6–8 h and 0.75 for ≥9 h ( P = 0.001). Conclusions: Our findings show an association between quality of life and sleep time among adult stroke survivors. Sleep time should be considered in efforts to improve stroke survivors' quality of life, including education and interventions that encourage 6–8 h of sleep. Geriatr Gerontol Int 2019; 19: 1226–1230 .